Reforma al art. 321 del Código Civil y Reforma el Literal 1 del Art. 168 del Código de la Niñez y Adolescencia para integrar, transparentar y agilitar el proceso de adopción en el Ecuador - Mena Molina, Francisco Xavier (2015)
Boys, girls and adolescents in our country that different situations have not been able to form a family, to have the opportunity to participate in adoption programs and improve their quality of life, emotional, economic and social. So the Constitution of the Republic of Ecuador, in Art. 44, expressed: "the State, society and the family will promote the comprehensive development of children and adolescents as a priority, and ensure the full exercise of their rights; you will attend at the beginning of their interests and their rights shall prevail over the other people The children and adolescents are entitled to their integral development, understood as a process of growth, maturation and deployment of his intellect and abilities, potential and aspirations, in a family, school, social and community environment of affection and security. This environment will allow the satisfaction of affective-emotional, cultural, and social needs with the support of national and local cross-sectorial policies So and to comply with provisions in the Constitution of the Republic; through the Ministry of Social and economic Inclusion with direct support of the INFA and covered in the corresponding legal regulations has been established at national and international adoption program. But analyzing carefully the legal regulations we have found that there are two items that need to be reformed; Thus the Civil Code, title XIV of the adoption The consent of the parents of the adoptee and adopter. If one parent has died or is legally unable to express his will, the consent of the other is sufficient. If they are separated or divorced, enough of those parents who have the parental authority, with approval of the unit technique of adoptions of the Ministry of Social Welfare, previous knowledge of the facts, and sending you hear another demonstrate its conformity or non-conformity with the Act of adoption..." Intends to modify the following: enough of those parents who have the parental authority, with approval of the unit technique of adoptions of the Ministry of Social. Welfare, previous knowledge of the facts, and sending you hear another demonstrate its conformity or non-conformity with the Act of adoption By foregoing manifests in the following way: Art. 321 for the adoption of a minor is required the will of the adoptive parent and the consent of the parents of the adoptee. If one parent has died or is legally unable to express his will, the consent of the other is sufficient. If they are separated or divorced, will equality will need to consent to the adoption, with approval of the technical unit of adoptions of the Ministry of Social Inclusion. The code on children and adolescents, chapter II, administrative phase; "Art 168.-of the units techniques of adoptions-corresponds to technical units of adoptions: develop or request and approve, reports medical, psychological, legal, family and social, concerning the person who is going to take;" and require expansions or clarifications that may be necessary." The analysis of these changes, to the Art. 321 aims to approve the procedure for the adoption of transparent, open and inclusive way and successfully re-collimating this requirement. Albeit the adoption in our country, today is a process never ends the modification to article 168 has as final object develop or request and approve of agile way and optimize the time, in order that the candidate be adopted is the foster care of a family, a home.